POKEDIS (PODCAST LEADERSHIP IN ISLAM) AS EDUCATION MEDIA ABOUT LEADERSHIP IN ISLAM FOR STUDENTS - Dinda Safitri; Afna Alida; Tias Siti Nurafifah; Ani Nur Aeni (Al-Risalah : Jurnal Studi Agama dan Pemikiran Islam, 2022)
Leaders according to Islam are very close to the figure of the Prophet Muhammad SAW who is a role model for Muslims. Leadership in Islam aims to show the way to Allah SWT and achieve His pleasure. As a leader, we must have 4 mandatory characteristics for the Apostle that we can emulate, including Siddiq, Amanah, Tabligh and Fathanah. In addition, a leader who should also have Islamic leadership qualities, namely fair, istiqamah, open and visionary. Many leaders do not imitate the Prophets and Apostles, especially among students. Therefore, the author conducted research on how the product that the author developed could educate students about leadership in Islam. The author's purpose is to find out how to design educational podcast media about Islamic leadership and find out podcast media products for education about Islamic leadership for students. In this study, the author uses a Design and Development (D&D) model research methodology using the ADDIE research procedure (Analyze, Design, Development, Implementation, and Evaluation) where researchers will design, develop and develop a product that has been developed, namely a podcast entitled "POKEDIS (Podcast Leadership in Islam). The results of the assessment of 55 student respondents that the POKEDIS product was highly accepted as a medium of education about leadership in Islam by 63.6% and several other students stated that it was acceptable with a score of 30.9%. So that the POKEDIS product that the author developed can be accepted as an educational medium about leadership in Islam. Pemimpin menurut Islam sangat erat kaitannya dengan sosok Nabi Muhammad SAW yang merupakan suri tauladan bagi umat muslim. Kepemimpinan dalam Islam bertujuan untuk menunjukkan jalan kepada Allah SWT dan mencapai ridha-Nya. Sebagai seorang pemimpin haruslah memiliki 4 sifat wajib bagi Rasul yang bisa kita teladani diantaranya Siddiq, Amanah, Tabligh dan Fathanah. Selain itu, pemimpin yang semestinya juga memiliki sifat-sifat kepemimpinan Islami yaitu adil, istiqamah, terbuka dan visioner. Banyak pemimpin yang tidak meneladani para Nabi dan Rasul terutama di kalangan mahasiswa. Maka dari itu, penulis melakukan penelitian tentang bagaimana produk yang penulis kembangkan bisa mengedukasi mahasiswa mengenai kepemimpinan dalam Islam. Tujuan penulis yaitu untuk mengetahui bagaimana desain media podcast edukasi mengenai kepemimpinan Islam dan mengetahui produk media podcast untuk edukasi mengenai kepemimpinan Islam bagi kalangan mahasiswa. Dalam penelitian ini, penulis menggunakan metodologi penelitian model Design and Development (D&D) dengan menggunakan prosedur penelitian ADDIE (Analyze, Design, Development, Implementation, and Evaluation) dimana peneliti akan merancang, mengembangkan dan mengevaluasi produk yang telah dikembangkan yaitu podcast yang berjudul “POKEDIS” (Podcast Kepemimpinan dalam Islam). Hasil penilaian dari 55 responden mahasiswa bahwa produk POKEDIS sangat diterima sebagai media pendidikan tentang kepemimpinan dalam Islam sebesar 63,6% dan beberapa mahasiswa lainnya menyatakan dapat diterima dengan skor 30,9%. Sehingga produk POKEDIS yang penulis kembangkan dapat diterima sebagai media edukasi mengenai kepemimpinan dalam Islam.